A study on antimicrobial sensitivity pattern in Neisseria gonorrhoeae in a tertiary care hospital - Shariff, V. N. S. Ahamed; Balamurugan, L. (International Journal of Research in Medical Sciences, 2017)
Background: Sexually transmitted diseases are prevalent throughout the world. Sexually transmitted diseases (STD) play a major role in the transmission of HIV infection. The risk of acquiring HIV infection in non-ulcerative STD is 3 to 5 times more than that in persons without any sexually transmitted infections. One of the main non-ulcerative STD is gonorrhoea. The relative incidence of gonococcal infections is about 10 to 13% of total sexually transmitted infections in STD clinics. Aims and objectives was to identify gonococcal infection in patients attending the STD clinic and associated sexually transmitted infections and to study the antimicrobial susceptibility of gonococcus and to modify the disease intervention strategies. Methods: A retrospective study was conducted in our institute of venereology, government general hospital and madras medical college, Chennai-03, Tamil Nadu, India. 43 patients with gram stained smear or culture positive for gonococcus who attended the institute from February 2013 to September 2014 were taken into the study. All the details were collected from the case records of the patients. The antibiotic sensitivity testing in N. gonorrhoeae had been done by Kirby-Bauer disc diffusion method. Screening for other sexually transmitted diseases had been done and were treated according to the institute guidelines. Results: Specimens from 43 patients (40 male, 3 females) had been collected. 40 specimens were found to be culture positive. Antibiotic sensitivity tests were carried out on those 40 isolates of Neisseria gonorrhoeae obtained in pure culture. 70% of isolates were resistant to penicillin and 30% were less sensitive to it. 52.5% of the isolates were PPNG. 57.5% of isolates were resistant to ciprofloxacin and 42.5% were less sensitive to it. 7.5% were resistant to ceftriaxone, 12.5% were resistant to cefixime and 15% were resistant to spectinomycin. All the isolates were sensitive to Azithromycin. Three male patients had HIV (6.9%), three had syphilis and one had genital wart. One female patient had trichomoniasis. Conclusions: The results of the study indicate that multidrug resistant Neisseria gonorrhoeae is prevalent in this region. Associated STDs must be investigated to prevent the transmission of HIV and further complications. The need for establishing a national surveillance programme for antibiotic resistance becomes clear with this study.